PENGARUH PEMUPUKAN N, P DAN K TERHADAP PRODUKTIVITAS DAN MUTU MINYAK Mentha arvensis - Oktivia Trisilawati; Ekwasita Rini Pribadi; Molide Rizal; Sintha Suhirman (JURNAL AGRONIDA, 2020)
Mentha arvensis is an annual herbaceous plant that produces cornmint oil used for  pharmaceutical and food industries. As a source of menthol and dimentolized oil, M. arvensis has a profitable opportunity to be cultivated in Indonesian agroclimate. The research was conducted to obtain the optimal dosages of N, P and K fertilizers, for increasing the yield and oil quality of M. arvensis, planted in Cicurug Research garden (latosol soil, 550 m asl.), by using randomized block design, with two factors, arranged factorially, with 3 replications.  First factor was M. arvensis promising number (Mear 0010 and Mear 0012), and fsecond factor was NPK fertilizer, included:  a). control, b). 69 kg N + 54 kg P2O5 + 94,5 kg K2O, c). 69 kg N + 72 kg P2O5 + 94,5 kg K2O, d). 69 kg N + 90 kg P2O5 + 94,5 kg K2O, e). 92 kg N + 90 kg P2O5 + 126 kg K2O, f). 92 kg N + 72 kg P2O5 + 126 kg K2O, and g). 138 kg N + 90 kg  P2O5 + 126 kg K2O per ha.  Variables observed were plant height, number of leaf and branch, biomass weight, oil content, free menthol content, and total menthol content.  The results showed that application of 92 kg N + 72 kg P2O5 + 126 kg K2O/ha equivalent to 200 kg Urea+ 200 kg SP-36 + 200 kg KCl/ha to M. arvensis, resulted better herb biomass, oil content, total menthol content and oil yield at first harvest compared with other fertilizer treatments.  At first harvest, oil and menthol yield were 41 and 25 kg / ha. The uptake of N, P, K nutrients were N > K > P, respectively.